Multiculturalism: a Malaysian perspective - Bakar, Osman (College of Religious Studies, Mahidol University & Konrad Adenauer Stiftung, 2018)
In this article, ethnic and religious diversity understood in the sense that we have just explained constitutes the core content of cultural diversity with which the notion of multiculturalism is basically concerned, particularly as applied to the Malaysian national context. The foregoing introductory passages in which we purposely make references to the religious dimension of cultural diversity, particularly to Islam, are meant to provide a pertinent background to our current discussion. Ethnic and religious diversity and pluralism and the challenges it poses to nation-building is a lingering issue in Malaysia ever since its independence from the British in 1957. Central to the national concern for peaceful ethnic and racial relations is the issue of the special rights and affirmative policies for Malays and other Bumiputera ethnic groups and the place and role of Islam vis-à-vis other religions in the country, particularly in the legal domain where there exists frequent tension and conflict between Islamic law (Shari’ah) and civil law. Since almost all Malays are Muslims, these delicate issues help propel Islam to the center stage of the national discourse and debates on ethnic and religious diversity and pluralism.